Re-Design Ruang Muat Kapal Alih Fungsi Barge Menjadi Oil Barge 5000 DWT - Urip Prayogi (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
Barge or Barge 5000 DWT is a means or means of sea transportation that contains coal. PT Maritim Transportindo is engaged in the shipping transportation industry, which provides barges to transport coal. Based on these problems, a redesign of the oil barge will be planned according to the BKI class standards. The results of planning using the standard empirical calculation method of BKI Vol II 2016, the results of the design of the load space obtained 5 loading spaces with each size of loading space, namely loading space 1 and 2 obtained 10,980 mm in length, 3 and 4 load spaces obtained 12,810 mm in length. , load space 5 is obtained 10,980 mm in length. Based on the planning of the loading and unloading system, the pump for loading and unloading system has a planned pipe diameter of 125 mm with a capacity of 2 main loading and unloading pumps, namely 218,382 m3 / hr with 2 hours of main pump power 14, 12 Kw. The capacity of the loading and unloading standby pump is 109.191 m3 / hr with a pump power of 7.0628 Kw.